Effect of Methyltrimethoxy Silane Modification on Yellowing of Epoxy Coating on UV (B) Exposure. (11th June 2014) - Rajagopalan, Narayani; Khanna, A. S.
Abstract : The exterior durability of epoxies is severely affected due to its poor weathering resistance. Epoxies exhibit chalking and discoloration under UV exposure caused as a result of photodegradation. The present work aims at studying the extent to which the color change and yellowing caused due to weathering under accelerated weathering conditions, of DGEBA epoxy, could be lowered by in situ modification of the epoxy polymer backbone with a silane, namely, MTMS. The epoxy resin and silane-modified epoxy resin were formulated into a TiO2 -based white coating, applied on mild steel panels, and exposed in a UV (B) weatherometer. The color change (dE) and yellowness index (YI) values of weathered panels were evaluated using a spectrophotometer. The weathered samples were also characterized using FTIR-imaging technique to study the effect of weathering on the structural backbone of the formulated coatings. The silane-modified epoxy coatings showed lowered yellowing by 45% on UV exposure and the enhanced resistance to yellowing of the modified coatings was indicated by lowered dE and YI values. The enhanced resistance to yellowing by the silane-modified epoxy was attributed to the strengthening of the epoxy backbone by introduction of Si–O–C linkage onto the epoxy polymeric chain.